ANALISIS PERAN PEMBIAYAAN MIKRO PERBANKAN SYARIAH ERHADAP MASYARAKAT PELAKU USAHA MIKRO (STUDI KASUS PADA BANK SYARIAH INDONESIA KCP BONE JEPPE’E) - keri, Ismail (Faculty of Islamic Economics and Business, 2022)
This study discusses the analysis of the role of Sharia financing on the community of micro-business actors in a study at Bank Syariah Indonesia KCP Bone Jeppee. The purpose of this study is to find out how the role of Sharia financing in the community of micro-entrepreneurs and how the operational standards of microfinance of Bank Syariah Bone branch. Based on the purpose of the study, this research is a type of research in the fieldfield research using a qualitative descriptive approach. This technique is used to describe the data researchers collected from the data from interviews during research at Bank Syariah Indonesia cab. Bone Jeppe'e. The results showed that Bank Syariah Indonesia was given a good role in the economic growth of the community and one of the financing roles given to the community, namely by providing capital loans for the community for the development of micro and medium enterprises around the Jeppe'eserta area as well as providing assistance and guidance by providing briefing to customers in the development of their business in order to develop for the better and The standard operating procedures for microfinance go through the market process stages, the initial process of collecting data on the financing analysis stage of the financing approval stage of the binding stage of the contract in the disbursement stage and the monitoring stage.